ANALISIS NILAI-NILAI KARAKTER DALAM LAGU “TIBA-TIBA” KARYA QUIIN SALMAN - Linda Sartika Aprilia; Sunan Baedhowi; Ari Widyaningrum (STKIP Subang, 2023)
This research was motivated by the emergence of modern love-themed songs which are often broadcast on television, Instagram and Tik Tok. The problem in this research is what character values ​​are contained in the song